1999
DOI: 10.1017/s0012162299001279
|View full text |Cite
|
Sign up to set email alerts
|

Modulations in breathing patterns during intermittent feeding in term infants and preterm infants with bronchopulmonary dysplasia

Abstract: As infants with bronchopulmonary dysplasia (BPD) have difficulty maintaining adequate levels of oxygenation during rest, it was decided to investigate how the additional respiratory demands associated with nutritive feeding disrupt their breathing rates. The sucking and breathing patterns of six (three male, three female) preterm infants (between 23 and 29 weeks gestational age at birth), classified as having BPD were individually compared with the patterns observed in 12 (six male, six female) healthy term (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…9 This may be because of issues such as irregular breathing patterns associated with oral feedings and/or delays in the normal maturation of stable suck/swallow rhythms. 16,17 Infants such as these may also benefit from a more individualized approach to oral feeding as our study proposes.…”
Section: Discussionmentioning
confidence: 95%
“…9 This may be because of issues such as irregular breathing patterns associated with oral feedings and/or delays in the normal maturation of stable suck/swallow rhythms. 16,17 Infants such as these may also benefit from a more individualized approach to oral feeding as our study proposes.…”
Section: Discussionmentioning
confidence: 95%
“…Craig et al found that babies with severe BPD had a lower tolerance for breathing pause during sucking and swallowing than term infants. The shorter than normal breath pauses in the BPD infants were followed by a period of irregular hyperventilation (Craig et al 1999). In some preterm infants, these periods of hyperventilation are followed by an apnea (Gryboski 1969).…”
Section: The Ventilatory Response To Hypoxiamentioning
confidence: 99%
“…36 It also reduces the risk of bradycardia and hypoxemia related to breathing irregularities common to preterm infants during bottle feeding. 11,12,[37][38][39][40][41][42] To prevent and/or minimize desaturation during feeding, Shiao and colleagues suggest a minimum baseline oxygen saturation of 95 percent prior to oral feeding. 12 To complete the first section of the EFS, the caregiver assesses the infant's readiness during preparation for feeding.…”
Section: Oral Feeding Readinessmentioning
confidence: 99%